(untitled) (CIPEEX, 2025)
Agribusiness contracts are essential to regulate commercial relations and ensure legal certainty between the parties involved. They can cover a variety of aspects, such as the purchase and sale of agricultural products, land leases, partnerships for cultivation, among others. This work aims to study the main contracts in the sector, such as purchase and sale, provision of services, lease and agricultural partnership, as well as the main clauses that corroborate their legal certainty. The methodology used was deductive, based on the analysis of the doctrines and legislation on the subject. As a result and discussions, it is important that the contract contains clear clauses on prices, deadlines, delivery conditions, responsibilities of the parties and penalties for non-compliance. Contracts must comply with current legislation, which may vary by country or region. In Brazil, for example, there are specific laws that govern agrarian and contractual issues. In addition, negotiation is an essential part of the contractual process. It is important that both parties feel comfortable and satisfied with the terms agreed upon. It is also important to explain that contract management consists of a set of administrative practices and actions that aim to monitor and validate all deliveries agreed upon in contracts. It is concluded that, in general, the contracts made by the agribusiness sector are important to build a good relationship with suppliers; negotiate payment terms; receive the necessary inputs and close important partnerships. A good contract provides legal certainty, minimizing risks and avoiding conflicts between the parties. In addition, good contract management ensures compliance with agreements and the satisfaction of both parties with the negotiation.